Call of greatness : milestone speeches and messages - Erguiza, Narciso Jr. (Quezon City, Philippines : Abiva Publishing House, Inc, 2017)
The idea of writing a compilation of speeches and messages was in the offing some years ago when my term as president of De La Salle University ended.
Dedication -- Introduction -- Foreword -- Chapter 1. Defining Greatness -- Chapter 2. Unleashing Greatness -- Chapter 3. Celebrating a century of greatness -- Afterword.
Keywords: EDUCATION